Pengaruh Waktu Kontak dan Bobot Biomassa Kangkung Air (Ipomoea aquatica) Terhadap Penurunan Kadar Total Suspended Solid (TSS) Air Limbah Rumah Sakit dengan Metode Fitoremediasi - Florensi Alya; Haryanto (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Hospital waste water is one of the causes of environmental pollution. Where river pollution is one of the effects (Sari et al., 2020). The high content of Total Suspended Solid (TSS) is the one of the parameters of river pollution. High TSS content in rivers has the potential to cause siltation (Ruhmawati et al., 2017). So that the management of hospital waste water is very important (Sari et al., 2020). One of the economical waste treatment methods is the phytoremediation (Novita et al., 2019). The research was conducted by mixing wastewater with acclimatized water (1:1), then 4 liters were taken and put into a container containing water spinach with a weight of (50, 100, 150, 200, 250) grams. Tests were carried out with variations in contact time (1, 2, 3, 4, 5) days. Samples were taken as much as 500 ml and then tested for its TSS content. It was concluded that contact time had an effect on decreasing TSS levels, while for biomass weight it had no effect. In addition, it was found that the effectiveness of water spinach in reducing the highest TSS level was 85% with a TSS level of 3 mg/L which occurred on a weight variation of 250 grams on the second day and at a weight of 100 and 200 grams on the third day, which means that water spinach was quite effective in reducing TSS levels in hospital wastewater.